The power of red: The influence of colour on evaluation and failure - A replication - Fikrlova, Jana; Cechova, Lenka; Lebedova, Tereza; Pycha, Patrik; Sesulkova, Alena; Prochazka, Jakub; Vaculik, Martin (Acta psychologica, 2019)
This replication of a study by >Rutchick, Slepian, and Ferris (2010) examines the influence of the colour of a pen on the activation of associations with failure and the focus on errors. We assigned two tasks to 198 students who completed them using either a red or a blue pen. The students were instructed to complete several word stems in the first task. In the second, we asked them to mark mistakes in a text. The participants using red pens completed significantly more word stems with words associated with failure than those using blue pens. The participants using red pens also marked significantly more mistakes in a text than those using blue pens. Our results support the findings of the original study and the hypothesized influence of the colour red in inducing a higher activation of associations with failure and a heightened focus on mistakes. Our study further contributes to research in this area in that it takes into account the participants' field of study and creates an explicit achievement context in which the observed phenomenon is most prevalent.
Keywords: Achievement; Random Allocation; Failure; Replication; mladiství; mužské pohlaví; Color; Adult; mladý dospělý; úspěšnost; barva; Achievement context; Red colour; Young Adult; ženské pohlaví; Humans; náhodné rozdělení; vnímání barev; Color Perception; dospělí; Female; Adolescent; lidé; Male